Neurobehavioural testing in workers occupationally exposed to lead: systematic review and meta-analysis of publications. Issue 4 (1st April 2002) - Goodman, M; LaVerda, N; Clarke, C; Foster, E D; Iannuzzi, J; Mandel, J
Abstract : Although the toxic effects of lead on the central nervous system have been well described, the blood concentration at which lead begins to exert adverse effects remains the focus of debate. A meta-analysis of occupational studies was conducted evaluating the association between neurobehavioural testing results and moderate blood lead concentrations.